Acquaintance rape the victims - Shapiro, Arnold; E. Glynn, Mary; AIMS Multimedia; Arnold Shapiro Productions ([S.l.] : Arnold Shapiro Productions, 2002)
This video present candid interviews to reconstruct four acquaintance rape cases and discusses the increased risks for those who use drugs and alchohol
Executive producer, Arnold Shapiro ; producer, Mary E. Glynn ; writer, director, Susan CArney ; editor, co-producer, Shirin Basleh
Narrator : Leeza Gibbons
Keywords: Rape Victims; Rape victims -- Interviews; Acquaintance rape victims; Sexual abuse victims